Monitoring the changes of germanium pollution in air and usability of Cedrus atlantica for pollution reduction - Ramazan ERDEM; Burak ARICAK; Semsettin KULAC (GSC Online Press, 2024)
Heavy metal pollution is a serious threat to living organisms and ecosystems worldwide. Therefore, it is of great importance to identify suitable biomonitors that can be used to monitor the changes in heavy metal pollution and hyperaccumulator species that can be used to reduce pollution. In this study, the usability of Cedrus atlantica in monitoring the change in the concentration of germanium (Ge) in air and reducing pollution was evaluated. In addition, Ge pollution in the last 60 years in Düzce province, where air pollution is at a very high level, was evaluated and the source of pollution was tried to be determined. As a result of the study, it was determined that the species is a suitable species that can be used both to monitor the change of Ge pollution in the air and to reduce this pollution. It was determined that Ge pollution increased significantly in the study area after 2013. The results of the study reveal that this pollution is mostly caused by traffic and urban areas.